Role of Surfactant during Microemulsion Photopolymerization for the Creation of Three-Dimensional Liquid Crystal Elastomer Microsphere Spatial Cell Scaffolds - Bera, Tanmay; Malcuit, Christopher; Clements, Robert J.; Hegmann, Elda (Frontiers in Materials, 2016)
Three-dimensional (3D) cell scaffolds based on connected nematic liquid crystal elastomer microsphere architectures support the attachment and proliferation of C2C12 myoblasts, neuroblastomas (SHSY5Y) and human dermal fibroblasts (hDF). The microsphere spatial cell scaffolds were prepared by an oil-in-water microemulsion photopolymerization of reactive nematic mesogens in the presence of various surfactants, and the as-prepared scaffold constructs are composed of smooth surface microspheres with diameter ranging from 10 to 30 μm. We here investigate how the nature and type of surfactant used during the microemulsion photopolymerization impacts both the size and size distribution of the resulting microspheres as well as their surface morphology, i.e. the surface roughness.